NILAI-NILAI DALAM TEKS CERITA PANGLIMO AWANG PADA TRADISI BUKOBA MASYARAKAT MELAYU PASIR PENGARAIAN SEBAGAI BAHAN AJAR BAHASA INDONESIA - -, Nisdawati (Edu Research, 2015)
Panglimo Awang story is a literary works of verbal. The narration of Panglimo Awang is a tradition of Malay culture that happens in Pasir Pengaraian. This research was written to describe the values contained in Panglimo Awang Narrative. This research is a qualitative research used descriptive analysis method of content descriptive analysis method . The object of this research is a narrative text of Panglimo Awang that data was collected from spiritual messenger called Tukang Koba . this research data is all of culture and education values that contained in opening sentences, utterance and character of figure in narrative text of PanglimoAwang.The result of this research is presented in form of cultural and education values as following: (1) cultural values about the essence of relationship between human and community with indicatorsrespect each others, responsible and advise, (2) the values of religious education with indicators namely believe in god, sincere and grateful, (3) the values of education such as, toughness, responsible, and hard working (4) thevalues of education concerns by indicators like polite, friendly, nation spirit, and forgiving. Those four cultural and educational values can be implemented in formal education, especially in learning Bahasa Indonesia.